2022
DOI: 10.1101/2022.10.29.514372
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prefrontal allopregnanolone mediates the adverse effects of acute stress in a mouse model of tic pathophysiology

Abstract: Ample evidence suggests that acute stress can worsen symptom severity in Tourette syndrome (TS); however, the neurobiological underpinnings of this phenomenon remain poorly understood. We previously showed that acute stress exacerbates tic-like and other TS-associated responses via the neurosteroid allopregnanolone (AP) in an animal model of repetitive behavioral pathology. To verify the relevance of this mechanism to tic pathophysiology, here we tested the effects of AP in a mouse model recapitulating the par… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Building on this finding, targeted striatal depletion of cholinergic interneurons (CINs) in adult mice has been shown to increase the frequency of self-grooming responses to environmental stressors 13 . We recently confirmed similar results in mice subjected to early-life CIN depletion (CIN-d) 14 . Notably, we found that the exaggerated grooming responses in CINd mice were reduced by benchmark therapies for tic disorders, such as the dopamine D2 receptor antagonist haloperidol 14 .…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…Building on this finding, targeted striatal depletion of cholinergic interneurons (CINs) in adult mice has been shown to increase the frequency of self-grooming responses to environmental stressors 13 . We recently confirmed similar results in mice subjected to early-life CIN depletion (CIN-d) 14 . Notably, we found that the exaggerated grooming responses in CINd mice were reduced by benchmark therapies for tic disorders, such as the dopamine D2 receptor antagonist haloperidol 14 .…”
Section: Introductionsupporting
confidence: 80%
“…We recently confirmed similar results in mice subjected to early-life CIN depletion (CIN-d) 14 . Notably, we found that the exaggerated grooming responses in CINd mice were reduced by benchmark therapies for tic disorders, such as the dopamine D2 receptor antagonist haloperidol 14 .…”
Section: Introductionsupporting
confidence: 80%
“…48 The responsiveness of CIN-d mice to D 1 R antagonists may be, similar to the observation in D1CT-7 mice, correlated with the stress response and increased neurosteroid allopregnanolone levels in the cortex. 48 Interestingly, a clinical trial using ecopipam for TS treatment also showed promising results. 49 Further investigation is needed regarding whether the D 1 R antagonist is beneficial only in TS patients under stress.…”
Section: Discussionmentioning
confidence: 52%
“…Another TS model is striatal ChI depletion mice (CIN-d mice) 12 with targeted ablation of 50$60% of ChIs in the dorsolateral striatum. They exhibited tic-like behaviors and significant PPI deficit 12 only under stress conditions, 48 which can be attenuated by haloperidol, SCH23390, and ecopipam, another D 1 R antagonist. 48 The responsiveness of CIN-d mice to D 1 R antagonists may be, similar to the observation in D1CT-7 mice, correlated with the stress response and increased neurosteroid allopregnanolone levels in the cortex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation